Time-inconsistent control problems, path-dependent PDEs, and neural network approximation - Nguwi, Jiang Yu (Nanyang Technological University, 2022)
There are two main parts of this thesis: Time-Inconsistent Control (TIC) problems (Chapters 1 and 2) and the neural network approximation (Chapters 3 and 4). In the first part of the thesis, we are interested in constructing and characterizing the equilibria of TIC problems, while in the second part of the thesis, we apply the neural network approach to solve path-dependent Partial Differential Equations (PDEs) and derive the generalization error bounds of 2-layer neural networks.